Municipal service delivery in Greater Tzaneen Local Municipality in Limpopo Province : a case of Lenyenye Township - Raophala, Matlhomoleng Hendrick (My University, 2013)
The research study attempts to understand levels of service delivery facing Lenyenye Township falling under the jurisdiction of Greater Tzaneen Local Municipal Council. The main focal point of the study is to ascertain the effectiveness of the provision of basic services such as electricity, water and roads by the Greater Tzaneen Local Municipality. This study takes into account that there are other townships such as Nkowankowa, Khutjwana and Tickeyline that are also under the jurisdiction of Greater Tzaneen Local Municipality, and therefore, the research made no attempts to compare levels of service in these towns as its main focus is Lenyenye Township. The findings of this case study are by no means a representation of the state of service delivery in the entire Greater Tzaneen Local Municipal area. The study is qualitative in nature as it attempts to understand how residents of Lenyenye Township perceive service delivery in their area. To get to the bottom of this investigation, interviews were conducted to supplement the data that is needed to make a case. The central elements of this study are community participation and financial management. According to White Paper on Local Government (1998), the above elements are the cornerstone of democracy, and that democracy should be visible and practical at grassroots. The study argued that provision of municipal services is also influenced by a high number of legislative frameworks some of which are still at a grappling stage by municipalities, for example; the implementation of White Paper on Transforming Public Service Delivery (1997). The study also discovered that a local sphere of government interacts with other organs of state, private sectors and non-governmental institutions in programmes and projects meant to advance the provision of municipal service. Greater Tzaneen Local Municipality like any other municipality is experiencing its fair share of the challenges such as financial management, community participation, and skills shortage. The study revealed that Lenyenye Township is experiencing poor service delivery from the municipality.
Thesis (MPA.) -- University of Limpopo, 2013
Keywords: Service delivery; Community participation; Municipal services -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo